Legal protection of consumers for transactions in counterfeit goods - Septiatiarini, Nadia; Aulia, Puput; Rahmawati, Sindy Dwi; Rahman, Alip; Dikrurahman, Diky (Indonesian Journal of Multidisciplinary Science, 2024)
This study examines the legal protection against consumers in Indonesia for the transaction of counterfeit goods. It uses normative legal research and everyday life studies to analyze the contemporary situation. The study reveals that legal protection against counterfeit goods is regulated by Law Number 15 of 2001, which criminalizes business actors selling counterfeit goods, and Government Regulation Number 82 of 2012, which emphasizes the need for accurate information about producers, goods supplied, and contract terms. Additionally, Article 8 of Law Number 8 of 1999 prohibits business actors from trading goods or services that do not meet the requirements for labels, information, advertising, or sales promotion.